Evaluating the Diagnostic Accuracy of Fine Needle Aspiration Cytology in Anaplastic Thyroid Carcinoma: A Case Report and Literature Review - Oktavia, Ria; Musyarifah , Zulda (Frontiers on Healthcare Research, 2025)
Background: Anaplastic thyroid carcinoma (ATC) is a rare and the most aggressive malignancies originating from the thyroid gland, characterized by rapid progression, local invasion, and a poor prognosis. Timely and accurate diagnosis of ATC is crucial for guiding appropriate management strategies and improving patient outcomes. Fine needle aspiration cytology (FNAC) is useful as a rapid  initial diagnostic tool for evaluating thyroid nodules and guiding subsequent clinical management. Methods: This case series aims to evaluate the diagnostic accuracy and correlation between FNAC and histopathological examination in cases of ATC. The study focuses on three patients, who were diagnosed with ATC from FNAC, followed by surgical resection with histopathological analysis. Results: . The patients, one male (44 years old) and two females (45 and 47 years old), exhibited cytological findings in Bethesda VI, malignant categories consistent with ATC. The histopathological examination revealed the tumor was Anaplastic Thyroid Carcinoma. Conclusion: This study demonstrates FNAC's have a consistent findings with histopathology in three patients. These serial cases showed that FNAC still valuable for initial diagnosis because exhibited consistent cytological and histopathological findings for diagnosis tool. A multimodal approach, clinical judgment and imaging, is recommended to enhance diagnostic precision.